Development of a new steel profile deck for composite floor system - Lim, Jia Ying. (2013)
Generally for ordinary profile steel deck, there are four possible modes of failure which are the bending moment failure at mid-span, shear failure at end support, web crippling and section failure over internal support under combined action of shear force and hogging moment. However, for this project, the author and her partner will be investigating on a newly developed steel deck using different codes of practice that has just been implemented recently by Building Construction Authority (BCA) in 2010. Hence, this report aims to investigate the behavior of the various modes of failure on a newly developed embossed profile steel deck through experimental studies and data analysis based on BS EN 1993-1-3 (Eurocode 3).